2010
DOI: 10.3855/jidc.1688
|View full text |Cite
|
Sign up to set email alerts
|

Anemia, leukocytosis and eosinophilia in a resource-poor population with helmintho-ectoparasitic coinfection

Abstract: Introduction: Eosinophilia and anemia are very common hematological alterations in the tropics but population-based studies scrutinizing their value for diagnosing parasitic infections are rare. Methodology: A cross-sectional study was conducted in a rural district in northeast Brazil where parasitic infections are common. Stool and blood samples were collected and individuals were clinically examined for the presence of ectoparasites. Results: In total, 874 individuals were examined. Infection with intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…However, there was no significant relationship between any of the ectoparasite infestations and the eosinophil count or hematocrit level. This is in accordance with Heukelbach et al (2006) and Pilger et al (2011) who reported that eosinophilia was not significantly associated with the presence of ectoparasites.…”
Section: Discussionsupporting
confidence: 81%
“…However, there was no significant relationship between any of the ectoparasite infestations and the eosinophil count or hematocrit level. This is in accordance with Heukelbach et al (2006) and Pilger et al (2011) who reported that eosinophilia was not significantly associated with the presence of ectoparasites.…”
Section: Discussionsupporting
confidence: 81%
“…For a diagnostic tool to be reliable it must have sensitivity and specificity of > 90% [15] and the elevated serum GR activity observed in this study satisfied this condition. In addition, high positive predictive value or precision obtained in this study agrees with high prevalence of falciparum malaria reported in the tropics [47] and implies that early treatment could be initiated in children after effectively diagnosing malaria using serum GR activity [48]. The high sensitivity, specificity, precision and odds ratio of the use of serum GR activity for diagnosis of falciparum malaria in children will reduce the use of antimalarial drugs in malaria negative cases (4% detected in this study) and the number of true malaria cases which are not treated (2% detected in this study).…”
Section: Discussionsupporting
confidence: 88%
“…Neutrophilia is a common indicator for an inflammatory response to an infectious or non-infectious origin. Likewise, eosinophilia is characteristic of allergic inflammation or parasites [33]. Both, neutrophilia and eosinophilia, are usually considered as indicators of a parasitic infection [34].…”
Section: Discussionmentioning
confidence: 99%